Current status and trends of acetylcholinesterase reactivators: the trimedoxime contribution - Polisel, Daniel Angelo (2022)
Organophosphorus compounds are compounds with high potential for toxicity in many living beings, especially in humans. These compounds class acts on the nervous system, inhibiting the acetylcholinesterase function, the enzyme responsible for the hydrolysis of the neurotransmitter acetylcholine, a natural process that controls the end of receptors ́ stimulation, controlling the nerve impulses transmission. With the acetylcholinesterase inhibition, there is no interruption of the nerve receptors interaction with acetylcholine, generating an overstimulation of these, resulting in control and coordination of muscles contractions trouble, known as cholinergic crisis. The lack of muscle contractions control compromises several body systems, in cases of acute intoxication, especially the respiratory system, leading the individual to death due to cardiorespiratory arrest. Despite the known health risks of organophosphorus compounds, they are present in society and are widely used in agriculture and veterinary medicine on several classes of pests controlling. In addition, throughout history, organophosphorus compounds have been extensively studied and used as chemical weapons, and their use has been confirmed in military conflicts and terrorist attacks. Bearing this in mind, the need for research and development of antidotes for intoxication by these compounds is a current demand, since current drugs are generally specific for certain organophosphorus and there is no broad- spectrum antidote. This work consists of two articles, the first being a literature review of main contributions in the inhibited acetylcholinesterase reactivation field, through different reactivators classes in recent years. The second article consists on the theoretical study, through computational modeling tools, of acetylcholinesterase inhibited reactivation process by both chemical weapons and pesticides representatives, through Trimedoxime, with results showing a good reactivation potential for the enzyme inhibited by VX. Furthermore, the thermodynamics parameters that govern the reactivation process contributions, through Trimedoxime, were discussed, aiming to advance in the understanding of the acetylcholinesterase inhibited reactivation process by different organophosphorus in the search for a broad-spectrum reactivator.